Tradisi Ancak sebagai Kearifan Lokal di Kelurahan Gebang, Jember - Syifa’, Muhammad Ali; Rizal, Syaiful (Proceedings of Annual Conference for Muslim Scholars, 2025)
The Ancak tradition in Gebang Village, Jember, is a local celebration of the Prophet Muhammad’s saw. birthday. The tradition plays an important role in building social harmony, strengthening relationships between residents, and fostering values of tolerance and togetherness in the midst of a diverse community. This study explores the tradition as an expression of social unity rooted in religious values. Using a qualitative case study method with participatory observation and in-depth interviews. The results show that the Ancak Tradition is not only a religious ritual but also a means of learning local character, including the value of tawassuth. The process from preparation to implementation of Ancak provides a profound educational experience while strengthening the cultural identity of the community. Thus, the Ancak Tradition is a concrete example of learning character values through local culture that supports religious moderation and social harmony in Gebang Village, Jember